Dynamic Changes in the Nigrostriatal Pathway in the MPTP Mouse Model of Parkinson’s Disease - Dongping Huang; Jing Xu; Jinghui Wang; Jiabin Tong; Xiaochen Bai; Heng Li; Zishan Wang; Yulu Huang; Yufei Wu; Mei Yu; Fang Huang (Parkinson's Disease)
The characteristic brain pathology and motor and nonmotor symptoms of Parkinson’s disease (PD) are well established. However, the details regarding the causes of the disease and its course are much less clear. Animal models have significantly enriched our current understanding of the progression of this disease. Among various neurotoxin-based models of PD, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model is the most commonly studied model. Here, we provide an overview of the dynamic changes in the nigrostriatal pathway in the MPTP mouse model of PD. Pathophysiological events, such as reductions in the striatal dopamine (DA) concentrations and levels of the tyrosine hydroxylase (TH) protein, depletion of TH-positive nerve fibers, a decrease in the number of TH-positive neurons in the substantia nigra pars compacta (SNpc), and glial activation, are addressed. This article will assist with the development of interventions or therapeutic strategies for PD.